Falciparum malaria case acquired by wound exposed to the blood of infected malaria patient - Hamdy Ibrahim; Safwat Abdel Maksod; Magdy Khorshed; Hanan Rady; Aadel Mohamed; Omar Alkassas; Marwa Haron; Suzan Saeed; Mohamed Mahmod; Khaled Ismail (SpringerOpen, 2024)
Abstract Malaria is a serious Anopheles mosquito-borne disease. It is not endemic in Egypt but continues to be imported by travelers returning from endemic areas. The transmission of malaria in non-endemic areas is an extremely unusual event, but it is possible under certain conditions. Herein, we report a case of prolonged fever in a patient living in the countryside of Egypt with no reported travel history following accidental blood exposure to a malaria patient. The purpose is to shed light on this rare mode of malaria transmission and also to alert physicians and infectious disease specialists to consider malaria in the differential diagnosis in case of contact history to the blood of a malaria patient.